Adding missing vines to the tree: multilocus phylogeny of New World vine snakes (Serpentes: Colubridae: Oxybelis), with description of a new species. Issue 31 (18th August 2021) - Torres-Carvajal, Omar; Mejía-Guerrero, Mauricio; Terán, Claudia
ABSTRACT: Neotropical vine snakes ( Oxybelis ) have a wide distribution range from southern United States to southeastern Brazil. Notably, the widespread brown vine snake O. aeneus was recently split into eight species, but major geographical areas such as the South American Pacific lowlands remained unsampled. In this paper, we present the largest molecular phylogeny of Oxybelis to date using six mitochondrial and nuclear genes and 10 of the 11 currently recognised species of Oxybelis . Our analyses include the first South American samples from west of the Andes, which we describe as a new species based on molecular and morphological evidence. The new species is morphologically most similar to O. acuminatus, O. aeneus, and O. inkaterra . Although the new species is genetically distinctive and divergent from its congeners, its phylogenetic placement received low support. Our results also suggest that a sample from Escudo de Veraguas Island in Panama represents an undescribed species of Oxybelis . Finally, we clarify the phylogenetic position of O. aeneus sensu stricto. https:urn:lsid:zoobank.org:pub:CC4E3741-D9DF-4F6C-8D0F-9BD20CB124E5